Profil darah ayam broiler fase finisher yang diberi ekstrak daun kelor (Moringa oleifera) dalam air minum: Blood profile of finisher phase broiler chickens given moringa leaf extract (Moringa oleifera) in drinking water - Sri Hartini; Martha Kayadoe; Dwi D. Rahardjo; Dwi Nurhayati (Fakultas Peternakan Universitas Papua, 2023)
Abstract The aim of the study was to determine the effect of Moringa oleifera (MO) leaf extract in drinking water on the blood profile of finisher broilers. A total of 140 broiler chickens at 21 days old were randomly allocated to 28 cages. Body weight per cage was 4433 ± 242.8 g (CV 5.48%). The experimental design was a completely randomized design with 4 (four) treatments and 7 replications. The four treatments were: P1 (1 L drinking water + 0 g MO leaves), P2 (1 L drinking water + 25 g MO leaves), P3 (1 L drinking water + 50 g MO leaves), and P4 (1 L drinking water + 75 g MO leaves). Moringa oleifera water was given with the patron of 3 days